Effect of external counterpulsation on running performance and perceived recovery - Russell, S.; Evans, A. G.; Jenkins, D. G.; Kelly, V. G. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To determine the efficacy of 20 minutes of external counterpulsation (ECP) on subsequent 1.2-km shuttle run test (1.2SRT) performance and perceived recovery following fatiguing high-intensity exercise. Methods: After familiarization, 13 recreationally active males (21.4?[1.9] y) participated in 2 experimental trials in a randomized crossover design. At 8:00 AM, participants completed a 1.2SRT, followed by an individualized high-intensity exercise bout and 20 minutes of ECP or supine passive rest (control). At 2:00 PM a second 1.2SRT was completed. Completion time for 1.2SRT (measured in seconds), heart rate, and Borg rating of perceived exertion were compared across conditions. Total quality of recovery and 100-mm visual analogue scale of perceived benefit of recovery were assessed at multiple time points. Results: A significantly smaller decline in PM 1.2SRT completion time compared with AM (baseline) was found for ECP compared with control (P=.008; moderate, very likely beneficial effect size of -0.77 [-1.53 to 0.05]). Total quality of recovery was significantly higher for ECP than control (P<.001), and perceived benefit of recovery was higher following ECP (P<.001, very large, most likely beneficial effect size of 2.08 [1.22 to 2.81]). Conclusions: Twenty minutes of ECP was found to be an effective recovery modality for within-day, between-bouts exercise, positively influencing subsequent 1.2SRT performance and enhancing perceptual recovery. ECP may be applied as a viable alternative to optimize and accelerate the recovery process, particularly in the event of congested training or competition demands.